Software Engineering Research, Management and Applications - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the outcomes of the 16th International Conference on Software Engineering, Artificial Intelligence Research, Management and Applications (SERA 2018), which was held in Kunming, China on June 13-15, 2018. The aim of the conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the various fields of computer science, to share their experiences, and to exchange new ideas and information in a meaningful way. The book includes findings on all aspects (theory, applications and tools) of computer and information science, and discusses related practical challenges and the solutions adopted to solve them. The conference organizers selected the best papers from those accepted for presentation. The papers were chosen based on review scores submitted by members of the program committee and underwent a further rigorous round of review. From this second round, 13 of the conference's most promising papers were then published in this Springer (SCI) book and not the conference proceedings. We eagerly await the important contributions that we know these authors will make to the field of computer and information science.
Temporal Locality with a Long Interval: Hybrid Memory System for High-Performance and Lowpower -- Design and Evaluation of A MMO Game Server -- Design and Evaluation of A MMO Game Server -- Interface Module for Emulator-based Web Application Execution Engine -- A Study on the Influence and Marketing Effect of Korean Wave Events and Festivals Organization -- Understanding the Success Factors of R & D Organization -- Study on Detection Algorithm of Live Animal in Self-Bag-Drop Kiosk in Airport Using UWB Radar.
Keywords: Computational intelligence; Software engineering; Artificial intelligence; Computational Intelligence; Software Engineering; Artificial Intelligence